Cracking behavior in reinforced concrete members with steel fibers: A comprehensive experimental study. (February 2015) - Tiberti, Giuseppe; Minelli, Fausto; Plizzari, Giovanni
Abstract: The addition of fibers in concrete determines a cracking phenomenon characterized by narrower and more closely spaced cracks, with respect to similar members without fibers. Fiber Reinforced Concrete (FRC) may significantly improve the tension stiffening into the undamaged portions of concrete among cracks, and, in addition, may provide noticeable residual stresses at a crack due to the bridging effect provided by its enhanced toughness. This paper aims at further investigating the ability of fibers in controlling cracks by discussing more than ninety tension tests on Reinforced Concrete (RC) prisms, carried out at the University of Brescia, having different sizes, reinforcement ratios, amount of fibers and concrete strengths. In particular the influence of FRC in reducing the crack spacing and the crack width is evaluated as a function of the FRC toughness. Finally, the most recent available models for predicting the crack spacing of FRC composites are evaluated and critically discussed. Highlights: Presentation of more than ninety tension tests on RC and SFRC prisms Presentation of a database on tension ties based on SFRC toughness Evaluation of the ability of SFRC in controlling cracking and reducing crack spacing Evaluation of recent available models for predicting the crack spacing of FRC